Coffee with Science: Instagram as a tool for scientific dissemination - Andrade Ávila, Renata; Elisiário Oliveira, Bárbara; Landim Fabiano, Maria Clara; dos Santos, Leonardo (Guará Journal, 2025)
Café com Ciência (Cafe with Science) is a proposal to use Instagram to popularize science, focusing on the @cafe.comciencia profile. The initiative, started by graduate students in 2019, was resumed in 2023 with the goal of facilitating public understanding of science through illustrated publications and accessible language. To this end, weekly posts were made on Instagram, addressing a variety of scientific topics, and the profile’s reach was assessed using the social network’s own metrics, such as reach and user engagement. The posts sought to connect research topics with the daily lives of followers, using polls and direct interactions to adapt the content. The results showed a significant increase in the number of followers and the reach of the posts, indicating the effectiveness of this approach in reaching and engaging the public. The highest engagement came from static posts that humanize scientists by showing them in their work environments. These results highlight the importance of social platforms for democratizing access to scientific knowledge, the need for clear and effective communication by scientists, and the potential of social media to establish a productive dialogue between the scientific community and the general public.